A Comprehensive Exploration of Internet of Digital Twins (IoDT) – Architecture, Applications, State-of-Art AI-based Solutions - Elmor, Alaa (International Journal of Computers and Informatics (Zagazig University), 2024)
Digital twins (DTs) have emerged as a powerful technology with wide-ranging applications across various fields including industry, healthcare, agriculture, smart city applications, etc. The convergence of Artificial Intelligence and the IoT with DTs can fulfill the system’s requirements in modeling and communication infrastructure. This convergence also enhances their potential by boosting predictive capabilities and facilitating data-driven decision-making. However, as DTs and AI are increasingly adopted, cybersecurity requirements have grown exponentially. In this study, the architecture and applications of the Internet of Digital Twins (IoDT) and review the state-of-the-art defense approaches. Lastly, we discuss research challenges and open research directions related to IoDT.